Upaya Guru Dalam Meningkatkan Kemampuan Kognitif Di Abad Ke-21 Pada Siswa Kelas V Madrasah Ibtidaiyah Daarul Hikmah Tangerang - Alfath Nurrahman; Moch Hasyim; Ali Aminullah; Anjar Sulistyani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Education is one of stages that must be passed in sharping the owned skill. Moreover in the 21st century, where every human is required to have the skill in their field, thus it is must be anticipated started from the childhood namely through primary education level. The main problem of this research how was the teachers’ effort in improving students’ cognitive skill through the basics of 21st century skill and how was the result of students’ cognitive skill improvement after the learning process was done. The purpose of this research was to find out what efforts done by teachers in improving the cognitive understanding skill of grade  V students during teaching and learning process activity and to find out the result of students’ cognitive skill improvement. The method used in this research was qualitative  descriptive where all problems existed would be discussed clearly. The techniques of data collection were observation, interview, and documentation. The subjects of this research were teachers of grade V MI Daarul Hikmah Tangerang. The results of this research showed that the effort done by teacher in overcoming the development occurred was by focusing on the three aspects of learning namely utilization of technology, usage of PAIKEM method in the KBM process and problem based learning. While the result obtained in the students’ cognitive improvement was increased from the previous score namely 1.840 to be 2.070.Keywords: Teacher, Students, Cognitive, The 21st Century